PENGELOLAAN KELAS RENDAH DALAM PEMBELAJARAN SDN PORIS PELAWAD 05 - Fadilah, Ahmad Arif; Rosita, Ria; Fadilah, Nur; Shadila, Bella; Berliana, Beta; Kusumawati, Putri Nur; Ezzafira, Rizka; Rizka, Saffana; Kusnadi, Devi; Mufidah, Wirdatul (Transpublika Publisher, 2022)
This study aims to determine the management strategy of low grade SDN Poris Plawad 05 Tangerang. This study uses a qualitative method by carrying out case observations. Data collection procedures were carried out through observation and interviews. Looking for some common data and detailed description references. The conclusion of this research is the making of lesson plans, planning for the new school year, semester programs and annual programs. Management is carried out through efforts to regulate students and good classroom facilities. Factors in the physical condition of the classroom and the creation of successful learning objectives that are fun. Meanwhile, the supervision is carried out by the class teacher to his students.